Development of a smart automatic internet of-thing - (IOT) - enabled clothes drying rack - Mohamad Akmal Aliff bin Azhari (2023)
It is always a challenge to dry washed clothed at the balcony during weekdays for working individuals and students who are mostly away during the day. A heavy afternoon torrential rain or thunderstorm could result in the drying clothes becoming wet again, wasting the energy and effort put into the washing.